1 PENEGAKAN HUKUM LINGKUNGAN TERHADAP KASUS PENCEMARAN LINGKUNGAN OLEH LIMBAH SABLON DI KABUPATEN BADUNG - Kusyadi, Anom Eka; Wairocana, I Gusti Ngurah; Sumerthayasa, Putu Gede Arya (Kertha Wicara : Journal Ilmu Hukum, 2012)
Developments in the residential neighborhood of Kuta area is notseparated from the rapid rate of population growth, population growth due toboth the city itself and because of urbanization. As we know also that the Kutaarea is one of the tourist destinations of Indonesia, has certainly done a lot ofdevelopment in the area that led to the attraction of the city is considered toprovide a better future for rural communities or outside the city. Variousdevelopment projects such as Hotel, Restaurant, Cafe, Disco, Bar, MoneyChanger, Mall and much more development can be established in the region to beable to support as one of the most visited tourist city and is required by foreignand local tourists. Along with population growth in the region, Variousdevelopment projects such as Hotel, Restaurant, Cafe, Disco, Bar, MoneyChanger, Mall and much more development can be established in the region to beable to support as one of the most visited tourist city and is required by foreignand local tourists. Along with population growth in the region will need for theprovision of infrastructure and housing will increase as well, either throughenhancements or new construction and industrial activities either by local ormodern technology can still be done. Further fulfillment of the needs ofresidential facilities and infrastructure both in terms of environmental complianceand affordable housing and livable yet fully provided by the community itself andthe government, so that the carrying capacity of the facilities and infrastructure ofexisting neighborhoods began to decline
Keywords: enforcement, environmental law, environmental pollution, waste silk screening